Singling out the effect of quenched disorder in the phase diagram of cuprates. (7th March 2019) - De Renzi, R; Coneri, F; Mezzadri, F; Allodi, G; Calestani, G; Righi, L; Lopez, G M; Fiorentini, V; Filippetti, A; Sanna, S
Abstract: We investigate the specific influence of structural disorder on the suppression of antiferromagnetic order and on the emergence of cuprate superconductivity. We single out pure disorder, by focusing on a series of samples at fixed oxygen content y    =  0.35, in the range . The gradual Y/Eu isovalent substitution smoothly drives the system through the Mott-insulator to superconductor transition from a full antiferromagnet with Néel transition K at z   =  0 to a bulk superconductor with superconducting critical temperature K at z   =  1, . The electronic properties are finely tuned by gradual lattice deformations induced by the different cationic radii of the two lanthanides, inducing a continuous change of the basal Cu(1)-O chain length, as well as a controlled amount of disorder in the active Cu(2)O2 bilayers. We check that internal charge transfer from the basal to the active plane is entirely responsible for the doping of the latter and we show that superconductivity emerges with orthorhombicity. By comparing transition temperatures with those of the isoelectronic clean system we determine the influence of pure structural disorder connected with the Y/Eu alloy.